Distribution of marine sand-dwelling dinoflagellates in Dinawan Island, Sabah - Abdul Latif, Asilah Al Has; Mohammad Noor, Normawaty (2011)
Sand-dwelling dinoflagellate species is important due to the capability of several species to produce toxin that may harm human being. distribution of marine sand dwelling dinoflagellates was investigated monthly from April 2009 to March 2010 in Dinawan ISland, Sabah. The main physicochemical parameters were also measured on every sampling dates. In this study, 20 dinaflagellates were identified based on Light Microscope (LM) and Scanning Electron Microscope (SEM) Prorocentrum rhatymum was commonly found at the sand samples collected. Relationship between the cells abudance and sand PH also were determined. Sand pH ranged 6.0 to 8.0. Knowledge on the distribution of sand-dwelling dinoflagellate speicies especially the toxin species are importnat for monitoring and management of harmful algal bloom.